For Example :-
(8)=3
(3)=0
For Example :-
B(3)=The Sum of the ones in binary of 3 which is (11) =2
B(6)=(110) =2
B(13)=(1101)=3
B(10)=2
If ( (n) ) =99B(x)
What is X=?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
E q u a t i o n 1 n = 1 ∑ X ( K 2 ( n ) ) = X-B(X)
By replacing n = 1 ∑ X ( K 2 ( n ) ) with 99B(X)
So 99B(X)=X-B(X)